Continuous EEG in Encephalitis - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Rady Children's Hospital of San Diego, CA, reviewed records from all 217 children enrolled in the California Encephalitis Project 2004-2011.